2017
DOI: 10.21767/1791-809x.1000518
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Stunting among Children of Age between 24 to 59 Months in Butajira Town and Surrounding District, Gurage Zone, Southern Ethiopia

Abstract: Background: Stunting is one of the major causes of morbidity and mortality among under-five children. It is used to assess nutritional status of children by measuring their length/height and age. The purpose of this study was to assess prevalence and factors associated with stunting among children of ages between 24 to 59 months in Butajira town and surrounding district, Gurage zone, Southern Ethiopia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 7 publications
1
21
0
4
Order By: Relevance
“…A multitude of studies have found similar associations [13,16,18]. This corroborates the ideas that stunting is a malnutrition which starts during pregnancy and continues until the second year of life with most frequent appearance after the second year of life [12].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…A multitude of studies have found similar associations [13,16,18]. This corroborates the ideas that stunting is a malnutrition which starts during pregnancy and continues until the second year of life with most frequent appearance after the second year of life [12].…”
Section: Discussionsupporting
confidence: 83%
“…The factors associated with stunting are very complex and interconnected with each other. The factors can be classified as distant factors, like socioeconomic status of the household, followed by intermediate factors, such as environmental factors and health service-related characteristics and immediate factors such as maternal, child and nutritional characteristics [6,[13][14][15][16][17]. A systematic review and meta-analysis of 21 studies in Africa found that the predictors of stunting were complementary feeding practice, maternal under nutrition, household food insecurity, economic growth, and maternal education, as principal determinants of stunting [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stunting is a public health and nutrition problem that sometimes is late to be recognised (Dewana, Fikadu, Facha, & Mekonnen, 2017). It has become a common problem in developing countries, as well as Indonesia.…”
Section: Discussionmentioning
confidence: 99%
“…2, Agustus 2018 P erawakan pendek mencerminkan kegagalan dalam menerima nutrisi yang cukup dalam jangka waktu lama. 1 Anak dengan tinggi badan berdasarkan usia (TB/U) <-2 Standar Deviasi (SD) menurut World Health Organization Chart Growth Standard dikatakan perawakan pendek. 2 Perawakan pendek merupakan salah satu masalah kesehatan di seluruh dunia dan mengenai 178 juta anak di bawah 60.…”
unclassified